The Effect of Imagery Training and Kinesthetic Perception on Zero-step Lay Up Shoot and Free-throw in Basketball Skills in Extracurricular Students of SMAN 2 Nganjuk - Vidi Geo Zulkarnain; Anung Priambodo; Abdul Rachman Syam Tuasikal; Raditya Pratama (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to determine the effect of imagery training (group 1), kinesthetic perception training (group 2), and control training (group 3) on improving zero-step lay-ups and free-throws. The method used in this research is an experiment with a quantitative approach with a research design using Match Subject Ordinal Pairing. The design in this study used 24 samples divided into 3 groups given different treatments. this study uses measurements of zero-step lay-up and free-throw. The results of this study indicate that the zero-step lay-up of group 1 has an average pre-test result of 76.75 the post-test results which are with an average result of 110.87, and free-throw group 1 with an average pre-test result of 36.62 for post-test with an average result of 71.25. With the conclusion that the zero-step lay-up increased by 44% and free-throw by 95%, from the pre-test and post-test results. The results of group 2 for zero-step lay-up training are with an average pre-test of 66.75 then for post-test results of 100.12, and for free-throw group 2 with an average of 44.62 then for post-test with an average of 72.5. The results of group 3 for zero-step lay-up training are with an average pre-test of 63.62 then for post-test results of 81.37, and for free-throw group 3 with an average of 38.62 then for post-test with an average of 60.12. With the conclusion that the zero-step lay-up increased by 28% and free-throw increased by 56% from the pre-test and post-test results. The control group did experience an increase because they continued to practice as usual without any treatment like groups 1 and 2, but the increase was still below that of the treatment group. Thus it can be concluded that imagery training and kinesthetic perception training can be used to improve the ability of zero-step lay-up and free-throw.